Daya Terima Pasien Kelas Iii Terhadap Menu Makanan Biasa Di RSUD Provinsi NTB - Puput Oktaviani; Luh Suranadi; AASP Chandradewi; Niketut Sri Sulendri (Poltekkes Kemenkes Mataram, 2018)
Background. The high leftovers in a hospital in result due to low patient acceptability . The low patient acceptability can be attributed to several factors other conduction of external factors and internal factors . External factors consist of food appearance and internal factors consist of appetite , eating habits , boredom , and the food from the outside. Research Methods. This study design using observational research is descriptive , based on time in terms of research using crossecectional approach , the target of this study is that patients who receive regular food menu in Provisinsi Mataram General Hospital who had been hospitalized at least 2 days . Samples were obtained as many as 27 samples. Research Result. the received power of regular meals judged on appearance ( color and texture ) food menu is still in the unattractive category because of the 5 -day menu shows the average percentage of less than 60 % . : the received power of regular meals judged on taste ( flavor and aroma ) food menu is still in the category of unattractive because of menu 5 days showed an average percentage of less than 60 %. Conclusion. The receive power to the appearance and the food taste in breakfast, lunch and dinner either from the first menu to the fifth menu still in the poor category because it is still less than 60 % .